The Nacala Corridor Railway and Port PPP project Risks identification research. Issue 4 (April 2020) - Jesus Rock, Elton De; Wu, Shulian
Abstract: Recently, Public Private Partnerships (PPP) in Mozambique has demonstrated significant advances in the level of private sector involvement in the delivery of infrastructure such as railways and port assets. It is generally considered that PPP is a mechanism to simplify the delivery of transportation projects, transfer the risks of transportation projects, reduce transportation costs and increase transportation revenue. This paper introduces a framework that identifies the risks associated with PPP arrangements for Railway and Port project delivery in Mozambique, with special attention to the Nacala corridor project. The framework divides risks into four categories: political, economic, socio-cultural, and technical (referred to as PEST), which can help project managers launch PPP projects to identify risks, manage risks, and minimize project risks.